Community policies on asylum and immigration - Pajares, Miguel Pajares (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Immigration and asylum policies came under the jurisdiction of the European Union after the coming into force of the Amsterdam Treaty in May 1999. From then onward, the European Commission has been submitting a series of proposals for the elaboration of future community regulations whose contents can be assessed, in general, positively (from the point of view of the immigrant and asylum applicants’ rights), even though not all proposals deserve this assessment. In this article, besides analysing these proposals, we consider the perspectives that exist for its approval, departing from the positions that the Council of Ministers for Justice and Home Affairs is having on these issues.